The Effect of Spiritual Mindfulness-Based Cognitive Therapy on Self-Concept and Risk of Depression in Adolescent at Islamic Boarding School - Fakhrun Nisa,; Fiddaroini,; Ah Yusuf,; Praba Diyan Rachmawati,; Yuni Sufyanti Arief,; Ferry Efendi,; Hari Basuki Notobroto, (Journal of Health Science Community, 2022)
The burden of the learning process and strict Islamic boarding school rules have an impact on self-concept and the risk of depression in adolescents. However, there is very limited research on how to solve academic pressure with the psychological impact of negative emotions and stress which significantly contribute to the development of mental health problems for adolescents in Islamic boarding schools. The purpose of this study was to determine the effect of spiritual mindfulness-based cognitive on self-concept and risk of adolescent depression. The research design used descriptive research. The population used in this study is the early adolescent girls at Middle School (SMP) Darul Lughah Wal Karomah Islamic Boarding School and Badridduja Islamic Boarding School Kraksaan Probolinggo who have a risk of depression. The sample size used was 219 adolescent girls using total sampling. The results showed that the results of a descriptive analysis on the risk of depression the majority were at moderate risk of depression in the emotional dimension was 32.4%, the self-concept variable in adolescents was at most self-concept while in the self-criticism dimension was 92.7%. The results of descriptive crosstab analysis on self-concept variables and the risk of depression in adolescents have the highest high self-concept with the risk of mild depression is 37.0% while the moderate self-concept in adolescents with the most risk of mild depression is 34.8%. The systematic review resulted in 25 articles that could be used to improve self-concept and reduce the risk of depression. Mindfulness-based cognitive therapy intervention was recommended to be applied by mental nurses as an intervention to improve self-concept and reduce the risk of depression in adolescents.